Optimal scheduling of integrated energy systems with exergy and demand responsiveness - Zhang, Baorui; Wang, Ruiqi; Wang, Ming; Wang, Mingyuan; Li, Ke; Yan, Yi; Gao, He (Frontiers in Energy Research, 2023)
To fairly use demand response to regulate customer load , support the economic and environmental protection, and assess the quantity and quality of the synergistic growth of the integrated energy system, a multi-objective optimum scheduling model and a solution method considering exergy efficiency and demand response are presented. To begin with, a mathematical model of each energy gadget is created. The electricity–gas load demand response model is then built using the price elasticity matrix, while the cooling load demand response model is built taking into account the user’s comfort temperature. On this basis, a multi-objective optimal dispatching model is developed with the optimization goals of minimizing system operation costs, reducing carbon emissions, and increasing exergy efficiency. Finally, the model is solved using NSGA-II to produce the Pareto optimal frontier solution set in various situations, and the VIKOR decision procedure is utilized to identify the complete best dispatching solution. The simulation results suggest that the proposed model can match the system’s scheduling needs in terms of numerous objectives such as economy, environmental protection, and exergy efficiency while also assuring user’s comfort.